Community Veterinary Medicine Programs: Pet Owners' Perceptions and Experiences - Kogan, Lori R.; Accornero, Veronica H.; Gelb, Emily; Slater, Margaret R. (Frontiers in Veterinary Science, 2021)
Many American pet owners struggle financially, and the COVID pandemic has only exacerbated this problem. Yet, the positive effects that companion animals have in people’s lives create the need for supportive systems to ensure that financial limitations, and other barriers, do not preclude pet ownership. To help address these barriers, and reach underserved communities, various forms of community-based veterinary medicine programs have been developed across the country. This study assesses two community based veterinary programs in North Carolina, USA. In addition to perceptions surrounding veterinary services, this study paid specific attention to communication and respect; two additional elements needed for successful community-based veterinary programs. Surveys were given to clients accessing The Asheville Humane Society (AHS) mobile veterinary care clinic and The Asheville Humane Society (AHS) Affordable Pet Care Clinic. Results of the anonymous survey indicate that the majority of clients had positive veterinary care experiences in terms of both veterinary services and client communication. They also noted a likelihood of seeking veterinary services in the future. In conclusion, low-cost community veterinary programs - with effective communication, empathy, and cultural competence - can help open the door to future positive veterinary experiences for disadvantaged pet owners.